2017
DOI: 10.1002/prp2.372
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with a selective PDE10A inhibitor TAK‐063 and either haloperidol or olanzapine at subeffective doses produces potent antipsychotic‐like effects without affecting plasma prolactin levels and cataleptic responses in rodents

Abstract: Activation of indirect pathway medium spiny neurons (MSNs) via promotion of cAMP production is the principal mechanism of action of current antipsychotics with dopamine D2 receptor antagonism. TAK‐063 [1‐[2‐fluoro‐4‐(1H‐pyrazol‐1‐yl)phenyl]‐5‐methoxy‐3‐(1‐phenyl‐1H‐pyrazol‐5‐yl)pyridazin‐4(1H)‐one] is a novel phosphodiesterase 10A inhibitor that activates both direct and indirect pathway MSNs through increasing both cAMP and cGMP levels by inhibition of their degradation. The activation of indirect pathway MSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…TAK‐063 at this dose did not exacerbate plasma prolactin levels and cataleptic response from antipsychotics in rats. Thus, TAK‐063 may produce augmented antipsychotic‐like activities in combination with antipsychotics without exacerbating side effects in rodents …”
Section: Combination Study Of Tak‐063 and Antipsychotics In Rodentsmentioning
confidence: 99%
“…TAK‐063 at this dose did not exacerbate plasma prolactin levels and cataleptic response from antipsychotics in rats. Thus, TAK‐063 may produce augmented antipsychotic‐like activities in combination with antipsychotics without exacerbating side effects in rodents …”
Section: Combination Study Of Tak‐063 and Antipsychotics In Rodentsmentioning
confidence: 99%
“…According to the pharmaceutical manufacturer (Avineuro) [227] Further development stopped because the primary endpoint of the assay was not reached [228] Selective dopamine D [274,275] Negative results from a phase II study [276] In one additional neuroimaging study on healthy male participants, TAK-063 attenuated ketamine-induced changes in…”
Section: Add Onmentioning
confidence: 99%
“…Up to now, these efforts have resulted in 12 reported clinical candidates and four clinically validated PDE10A PET ligands [ 273 , 274 ]. Following positive preclinical studies [ 275 ], which indicated efficacy in the treatment of positive and cognitive schizophrenia symptoms, the selective PDE10A inhibitor TAK-063 was investigated in a phase II study (20 mg/day, n = 83). Despite not meeting the primary endpoint, the authors stated that the results might be suggestive of antipsychotic activity [ 276 ].…”
Section: Pde Inhibitorsmentioning
confidence: 99%
“…Upregulation of cyclic nucleotide levels in indirect pathway MSNs could be an alternative approach for novel antipsychotics [ 20 , 21 ], whereas activation of direct pathway MSNs could be associated with improvement of cognitive functions. Thus, in contrast to the marketed antipsychotics, phosphodiesterase inhibitors (PDEIs) influence both the indirect and direct pathways, and the additional action of these compounds on the direct pathway could help distinguish them clinically from D 2 antagonists [ 22 ]. Moreover, PDEIs may have potential therapeutic utility in the treatment of cognitive impairment associated with schizophrenia or may be useful as an adjunctive treatment for negative symptoms in patients with schizophrenia [ 19 ].…”
Section: Introductionmentioning
confidence: 99%